2004
DOI: 10.1002/mrd.20134
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ca2+‐dependent calmodulin‐binding proteins in rat spermatogenic cells as complexes of the heat‐shock proteins

Abstract: Ca2+-calmodulin (CaM)-binding proteins in rat testes were characterized by assays for CaM-binding activity using the CaM-overlay method on transblots of electrophoresed gels and purification by gel-filtration, ion exchange, and adsorption chromatographies. A major CaM-binding protein complex (CaMBP) was identified and found to be comprised of three proteins with molecular masses 110, 100, and 70 kDa. Amino acid sequence analyses of lysylendopeptidase digests from these proteins indicated that all of the consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Determination of sperm motility revealed that the progressive movement was abolished in a significant number of spermatozoa from both fertile and subfertile Hspa4l Ϫ/Ϫ mice. The striking feature of reduced sperm motility can be due either to a possible structural defect or to a functional blockade in a physiological process leading to modulin (CaM) binding proteins in spermatogenic cells (19). CaMs regulate the activity of enzymes such as adenylate cyclases (8,18) and protein kinases (10), which are involved in the regulation of flagellum bending (5,28).…”
Section: Discussionmentioning
confidence: 99%
“…Determination of sperm motility revealed that the progressive movement was abolished in a significant number of spermatozoa from both fertile and subfertile Hspa4l Ϫ/Ϫ mice. The striking feature of reduced sperm motility can be due either to a possible structural defect or to a functional blockade in a physiological process leading to modulin (CaM) binding proteins in spermatogenic cells (19). CaMs regulate the activity of enzymes such as adenylate cyclases (8,18) and protein kinases (10), which are involved in the regulation of flagellum bending (5,28).…”
Section: Discussionmentioning
confidence: 99%
“…Although cyclin B1 can substitute cyclin B2 and the expression level of cyclin B1 did not change in 15-day Spo11 testes, still Ccnb1/Cdk1 complex can be compromised by downregulation of the expression of some genes. Among them, we found calmodulin, a gene that can affect cyclinB1/Cdk1 (also known as Cdc2) through its partner, the testis-specific heat-shock protein Hsp70-2 (Zhu et al 1997, Moriya et al 2004. Hsp-70-2 deficient mice exhibit failed meiosis (Dix et al 1996) and it has been suggested that Hsp-70-2 functions as a molecular chaperone for the Ccnb1/Cdk1 (Cdc2) complex (Zhu et al 1997).…”
Section: Gene Expression Profiles Of Spo11mentioning
confidence: 99%
“…Hspa2 deWciency is associated with male infertility due to failure of meiosis . Rodent's Hspa2 was found in complexes with Msj1 (Dnajb3, murine DnaJ homologue expressed speciWcally in adult testis; Berruti and Martegani 2001), and with calmodulin (CaM; Moriya et al 2004). Moreover, human HSPA2 protein was identiWed as a sperm-speciWc creatine kinase M-isoform, and the low level of HSPA2 apparently resulted in a defect of sperm development in the last phase of spermiogenesis (Huszar et al 2000).…”
Section: Introductionmentioning
confidence: 97%